2023
DOI: 10.20944/preprints202301.0302.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ferroptosis and Senescence: A Systematic Review

Abstract: Background: Senescence is a cellular ageing process in all multicellular organisms. It is characterized by a decline in cellular functions and proliferation, resulting in increased cellular damage and death. This condition plays an essential role in the ageing process and significantly contributes to the development of age-related complications. On the other hand, ferroptosis is a systemic cell death characterized by excessive iron accumulation followed by the generation of reactive oxygen species (ROS). Oxida… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 57 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Ferroptosis, a type of programmed cell death first described in 2012 (Dixon et al, 2012), involves lipid peroxidation generated by the iron overload, leading to cell swelling, mitochondrial dysfunction, nuclear chromatin condensation, and, finally, cellular membrane rupture (Han et al, 2020). Various studies have shown a correlation between the accumulation of iron in the brain which means increased ferroptosis and aging (Coradduzza et al, 2023), cerebrovascular diseases (Liu et al, 2022), and neurodegenerative diseases (including AD) (Ma et al, 2022). However, the exact molecular mechanisms of iron-induced neurodegeneration remain incompletely known.…”
Section: Iron Dyshomeostasis In Alzheimer's Diseasementioning
confidence: 99%
“…Ferroptosis, a type of programmed cell death first described in 2012 (Dixon et al, 2012), involves lipid peroxidation generated by the iron overload, leading to cell swelling, mitochondrial dysfunction, nuclear chromatin condensation, and, finally, cellular membrane rupture (Han et al, 2020). Various studies have shown a correlation between the accumulation of iron in the brain which means increased ferroptosis and aging (Coradduzza et al, 2023), cerebrovascular diseases (Liu et al, 2022), and neurodegenerative diseases (including AD) (Ma et al, 2022). However, the exact molecular mechanisms of iron-induced neurodegeneration remain incompletely known.…”
Section: Iron Dyshomeostasis In Alzheimer's Diseasementioning
confidence: 99%
“…The primary goal of cancer treatment research has been to eliminate malignant cells while protecting healthy cells (Cassetta and Pollard, 2023). To prevent the uncontrolled growth of cancer cells and other abnormal tissues, the body relies on a process known as "regulated cell death" (RCD) to keep things in check (Coradduzza et al, 2023;Huang et al, 2023). Apoptosis, paraptosis, necroptosis, and ferroptosis are among the distinct modes of RCD that have been characterized so far (Tong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress plays an essential role in cancer development and progression since high levels of reactive oxygen species (ROS) can trigger damage to biomolecules, promoting carcinogenesis (Cheung and Vousden, 2022). On the other hand, this metabolic imbalance may result in cell death by different mechanisms, becoming the induction of oxidative stress a potential strategy in anticancer therapy (Luo et al, 2022;Coradduzza et al, 2023).…”
mentioning
confidence: 99%